Digital transformation and strategy in the banking sector: Evaluating the acceptance rate of e-services - Fotis Kitsios; Ioannis Giatsidis; Maria Kamariotou (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Digital transformation in the banking sector is a continuous process that affects both the external and internal environment by redesigning internal processes and existing methods. There are many reasons that digital transformation takes place, such as servicing remote areas without physical branches, differentiation from competitors or reduction of operating costs. In any case, there are a lot of doubts about the acceptance of digital technologies. Thus, this article examines the acceptance rate of digital transformation in the banking sector in Greece. One hundred and sixty-one employees at Greek banks completed the survey. A Multivariate Regression Analysis was implemented to analyze the items of the Technology Acceptance Model. The findings of this paper indicate the perception of bank employees with regard to new technologies. This paper provides a practical contribution for executives of Greek banking organizations to schedule targeted educational programs to facilitate the transition to the new digital era for their employees. Executives are curious if employees are ready to accept and implement digitalization in their daily job routine. Therefore, the Technology Acceptance Model can provide answers to executives in facing these challenges.
Keywords: 650; business model; digital banking; digital strategy; digital transformation; e-services; technology acceptance model; user's intention